Anti-CD74 IgA antibodies show diagnostic potential for axial spondyloarthritis but are not associated with microscopic gut inflammation. (4th July 2022) - De Craemer, Ann-Sophie; Witte, Torsten; Lobaton Ortega, Triana; Hoorens, Anne; De Vos, Martine; Cuvelier, Claude; Vastert, Sebastiaan J; Baraliakos, Xenofon; Van den Bosch, Filip; Elewaut, Dirk
Abstract: Objectives: Gut inflammation commonly occurs in axial SpA (axSpA), and is linked to disease activity and outcome. Given the role of IgA in mucosal immunity, we explored the association between anti-CD74 IgA antibodies, gut inflammation and axSpA. Methods: Anti-CD74 IgA was measured by ELISA in serum samples of axSpA patients, fulfilling the 2009 Assessment of SpondyloArthritis international Society classification criteria. A group of fibromyalgia (FM) and RA patients served as non-inflammatory and inflammatory controls. Newly diagnosed axSpA patients underwent ileocolonoscopy; mucosal biopsies were histopathologically assessed as normal, acute or chronically inflamed. Optimal anti-CD74 IgA cut-off values were determined with a receiver operating characteristics curve. Results: axSpA patients ( n = 281) showed higher anti-CD74 IgA levels [mean (s .d .) 18.8 (12.4) U/ml] compared with 100 FM patients [10.9 (5.0) U/ml, P < 0.001] and 34 RA patients [13.7 (9.6) U/ml, P = 0.02]. The area under the receiver operating characteristics curve for diagnosis (axSpA vs FM) was 0.70, providing a sensitivity of 60% and specificity of 87% (cut-off 15 U/ml). Antibody concentrations were not significantly different between axSpA patients with ( n = 40) and without ( n = 69) gut inflammation ( P = 0.83), yielding an area under the receiver operating characteristics curve of 0.51. Anti-CD74 IgA levels were not associated with degree of bone marrow oedema on MRI of the sacroiliac joints, CRP or any other disease-specific feature such as the use of NSAIDs or biological treatment. Conclusion: Serum anti-CD74 IgA is a potentially useful diagnostic biomarker for axSpA. However, antibody levels do not correlate with any phenotypical feature, including microscopic gut inflammation, suggesting this to be a disease-specific rather than an inflammatory marker.